OpenCV 4 with Python blueprints become proficient in computer vision by designing advanced projects using OpenCV 4 with Python 3.8 - Gevorgyan, Menua (Packt Publishing, 2020)
OpenCV 4 with Python Blueprints demonstrates how to develop a series of intermediate to advanced projects using OpenCV and Python, rather than teaching the core concepts of OpenCV in theoretical lessons. and allow you to understand the foundations and approaches used in modern computer vision.